Cardiometabolic Phenotypic Differences in Male Offspring Born to Obese Preeclamptic-Like BPH/5 Mice - Beckers, Kalie F.; Gomes, Viviane C. L.; Crissman, Kassandra J. Raven; Adams, Daniella M.; Liu, Chin-Chi; Del Piero, Fabio; Butler, Scott D.; Sones, Jenny L. (Frontiers in Pediatrics, 2021)
Preeclampsia (PE) is a hypertensive disorder of pregnancy occurring in approximately 10% of women worldwide. While it is life threatening to both the mother and baby, the only effective treatment is delivery of the placenta and fetus, which is often preterm. Maternal obesity is a risk factor for PE, and the effects of both on offspring are long standing with increased incidence of cardiometabolic disease in adulthood. Obese BPH/5 mice spontaneously exhibit excessive gestational weight gain and late-gestational hypertension, similar to women with PE, along with fetal growth restriction and accelerated compensatory growth in female offspring. We hypothesized that BPH/5 male offspring will demonstrate cardiovascular and metabolic phenotypes similar to BPH/5 females. As previously described, BPH/5 females born to ad libitum-fed dams are overweight with hyperphagia and increased subcutaneous, peri-renal, and peri-gonadal white adipose tissue (WAT) and cardiomegaly compared to age-matched adult female controls. In this study, BPH/5 adult male mice have similar body weights and food intake compared to age-matched control mice but have increased inflammatory subcutaneous and peri-renal WAT and signs of cardiovascular disease: left ventricular hypertrophy and hypertension. Therefore, adult male BPH/5 do not completely phenocopy the cardiometabolic profile of female BPH/5 mice. Future investigations are necessary to understand the differences observed in BPH/5 male and female mice as they age. In conclusion, the impact of fetal programming due to PE has a transgenerational effect on both male and female offspring in the BPH/5 mouse model. The maternal obesogenic environment may play a role in PE pregnancy outcomes, including offspring health as they age.